Kinetic Study of the Leaching of Iraqi Akashat Phosphate Ore Using Lactic Acid - Eisa, Mohammed Y.; Abdulmajeed, Basma A.; Hawee, C. K. (Al-Khwarizmi Engineering Journal, 2018)
In the present work, a kinetic study was performed to the extraction of phosphate from Iraqi Akashat phosphate ore using organic acid. Leaching was studied using lactic acid for the separation of calcareous materials (mainly calcite). Reaction conditions were 2% by weight acid concentration and 5ml/gm of acid volume to ore weight ratio. Reaction time was taken in the range 2 to 30 minutes (step 2 minutes) to determine the reaction rate constant k based on the change in calcite concentration. To determine value of activation energy when reaction temperature is varied from 25 to 65 , another investigation was accomplished. Through the kinetic data, it was found that selective leaching was controlled by surface chemical reaction. The study showed that the reaction kinetics was specifically described by the shrinking core model (SCM). Regression analyses gave values of activation energy (Ea) and Arrhenius constant (ko) as 40.108 KJ/mole and (2.256 103 sec-1) respectively.